Impact of PPE availability and safety training on occupational health implementation in rural construction projects: a cross-sectional study - Yusriyanto; Asran (LPPM Politeknik Sandi Karsa, South Sulawesi, Indonesia, 2025)
Introduction: The construction sector remains one of the most hazardous industries worldwide, with significantly higher rates of fatal and major injuries. In Indonesia, construction accidents contribute to a considerable proportion of national occupational incidents. This study evaluates the implementation of Occupational Health and Safety (OHS) programs in a rural water supply infrastructure project. Method: A cross-sectional quantitative study was conducted involving 54 construction workers selected through total sampling. The study assessed Personal Protective Equipment (PPE) availability, PPE usage, and OHS training participation. Data were collected through structured interviews and direct observation. Statistical analysis was performed using the Chi-Square test with a significance level of 0.05. Results: The study found significant associations between OHS program implementation and PPE availability (p = 0.003), PPE usage (p = 0.001), and OHS training (p = 0.008). Workers with complete PPE availability and proper usage and those who had received safety training demonstrated a higher adherence to OHS protocols. Conclusion: The successful implementation of OHS programs in construction sites, particularly in rural water infrastructure projects, relies heavily on the availability and use of PPE and structured safety training. Strengthening these components can lead to a safer work environment and significantly reduce workplace accidents.